Using the EBSCO Database in the Area III Polyclinic of Cienfuegos in 2009 - Beatriz María Fúster Cabrera; Regla Pérez Águila; María Elinor Dulzaides Iglesias (Medisur)
Background: EBSCO is the full text database that provides relevant information related to biomedical sciences. It contains excellent collections, very helpful for professional practice and research. Objective: To revise how professionals and students of the ¨Cecilio Ruíz de Zárate ¨ Polyclinic, in Cienfuegos, use the EBSCO database and to develop informative skills in order to access all these information from the library. Method: An exploratory descriptive research was conducted in order to revise how professionals and students of the ¨Cecilio Ruíz de Zárate¨ Polyclinic, in Cienfuegos, used the EBSCO database in 2009 and to design a course in order to develop information skills to access EBSCO from the library. Results: 11.4% access EBSCO through he library’s bibliographic fund, which demonstrates total ignorance. Only 36.9% use the database for assistance-related questions and 25.5% for academic work, while 48.9% of participants never use the database at all and 63.2% declares to have limited skills. Conclusion: It is obvious that skills required to exploit the possibilities offered by EBSCO have not been developed in students and professionals, even though the Health Ministry pays a high fee to provide this free access.